Restrained Isolate Edge Geodetic Number of a Graph (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Here we study the new concept of restrained isolate edge geodetic set for a graph  of order . The edge geodetic set  of a connected graph  is said to be a restrained isolate edge geodetic set if the induced sub graph  has at least one isolate vertex and the induced sub graph  has no isolate vertex. The restrained isolate edge geodetic number denoted by  is the minimum cardinality of a restrained isolate edge geodetic set of . Here we determine the restrained isolate edge geodetic number of some standard graphs and by adding leaf vertices to a graph . In addition, we determine the restrained isolate edge geodetic number for some graphs using cartesian product and corona product.